Pengaruh kualitas dan durasi tidur terhadap regulasi emosi pada mahasiswa - marsilla, hana (Maliki Interdisciplinary Journal, 2026)
Sleep is a fundamental need that plays an essential role in maintaining cognitive and emotional functioning, particularly among university students who face various academic and social demands. This study aims to examine the influence of sleep quality and sleep duration on students’ emotion regulation. The research employs a descriptive approach that integrates theoretical insights with findings from previous empirical studies. The results indicate that sleep quality has a stronger impact on emotion regulation compared to sleep duration. Students with good sleep quality tend to exhibit greater emotional stability, better control over negative impulses, and more adaptive responses to stress. Meanwhile, sleep duration shows more variable effects; both insufficient and excessive sleep may affect emotional stability, although the outcomes are not always consistent. Overall, healthy sleep patterns—characterized by good sleep quality and adequate duration—serve as an important factor in supporting students’ psychological well-being. These findings are expected to serve as a reference for students and educational institutions in promoting healthier sleep habits to improve emotion regulation and academic performance.